Perlindungan Nelayan Lokal Sebagai Strategi Preventif Terhadap Praktik Illegal Fishing - Ilham Jayadi; Tara Claudya Framesty; Veronika Carolina Sitinjak; Adhitya Pratama (GLOBAL SCIENTS PUBLISHER, 2026)
Illegal fishing constitutes a real threat to Indonesia's marine resource sovereignty and the livelihoods of millions of local fishermen. This study examines two main issues: (1) the forms of legal protection afforded to local fishermen in confronting illegal fishing; and (2) the factors underlying the persistence of illegal fishing in waters serving as traditional fishing grounds of local fishermen. The method employed is normative legal research using a statute approach and conceptual approach. Findings indicate that legal protection for local fishermen has been accommodated in Law Number 45 of 2009 on Fisheries, Law Number 7 of 2016 on the Protection and Empowerment of Fishermen, and UNCLOS 1982, yet implementation continues to face structural obstacles. The persistence of illegal fishing is driven by limited surveillance capacity, institutional fragmentation, regulatory gaps, disproportionate economic incentives, and organized transnational fisheries crime networks. This research recommends strengthening the synergy between law enforcement, community-based empowerment, modernization of technology-based monitoring, and intensified international cooperation.